Smurf1 and Smurf2 mediated polyubiquitination and degradation of RNF220 suppresses Shh-group medulloblastoma - Yuwei Li; Huishan Wang; Bin Sun; Guifeng Su; Yu Cang; Ling Zhao; Shuhua Zhao; Yan Li; Bingyu Mao; Pengcheng Ma (Cell Death and Disease, 2023)
Abstract Sonic hedgehog (Shh)-group medulloblastoma (MB) (Shh-MB) encompasses a clinically and molecularly distinct group of cancers originating from the developing nervous system with aberrant high Shh signaling as a causative driver. We recently reported that RNF220 is required for sustained high Shh signaling during Shh-MB progression; however, how high RNF220 expression is achieved in Shh-MB is still unclear. In this study, we found that the ubiquitin E3 ligases Smurf1 and Smurf2 interact with RNF220, and target it for polyubiquitination and degradation. In MB cells, knockdown or overexpression of Smurf1 or Smurf2 promotes or inhibits cell proliferation, colony formation and xenograft growth, respectively, by controlling RNF220 protein levels, and thus modulating Shh signaling. Furthermore, in clinical human MB samples, the protein levels of Smurf1 or Smurf2 were negatively correlated with those of RNF220 or GAB1, a Shh-MB marker. Overall, this study highlights the importance of the Smurf1- and Smurf2-RNF220 axes during the pathogenesis of Shh-MB and provides new therapeutic targets for Shh-MB treatment.